Medical sequencing of candidate genes for nonsyndromic cleft lip and palate - Vieira, Alexandre R. (2019)
Nonsyndromic or isolated cleft lip with or without cleft palate (CL/P) occurs in wide geographic distribution with an average birth prevalence of 1/700. We used direct sequencing as an approach to study candidate genes for CL/P. We report here the results of sequencing on 20 candidate genes for clefts in 184 cases with CL/P selected with an emphasis on severity and positive family history. Genes were selected based on expression patterns, animal models, and/or role in known human clefting syndromes. For seven genes with identified coding mutations that are potentially etiologic, we performed linkage disequilibrium studies as well in 501 family triads (affected child/mother/father). The recently reported MSX1 P147Q mutation was also studied in an additional 1,098 cleft cases. Selected missense mutations were screened in 1,064 controls from unrelated individuals on the Centre d’E´tude du Polymorphisme Humain (CEPH) diversity cell line panel. Our aggregate data suggest that point mutations in these candidate genes are likely to contribute to 6% of isolated clefts, particularly those with more severe phenotypes (bilateral cleft of the lip with cleft palate). Additional cases, possibly due to microdeletions or isodisomy, were also detected and may contribute to clefts as well. Sequence analysis alone suggests that point mutations in FOXE1, GLI2, JAG2, LHX8, MSX1, MSX2, SATB2, SKI, SPRY2, and TBX10 may be rare causes of isolated cleft lip with or without cleft palate, and the linkage disequilibrium data support a larger, as yet unspecified, role for variants in or near MSX2, JAG2, and SKI. This study also illustrates the need to test large numbers of controls to distinguish rare polymorphic variants and prioritize functional studies for rare point mutations.